Combined MPM-DEM for Simulating the Interaction Between Solid Elements and Fluid Particles (Communications in Computational Physics, 2018)
How to effectively simulate the interaction between fluid and solid elementsof different sizes remains to be challenging. The discrete element method (DEM) hasbeen used to deal with the interactions between solid elements of various shapes andsizes, while the material point method (MPM) has been developed to handle the multiphase(solid-liquid-gas) interactions involving failure evolution. A combined MPM-DEMprocedure is proposed to take advantage of both methods so that the interactionbetween solid elements and fluid particles in a container could be better simulated.In the proposed procedure, large solid elements are discretized by the DEM, whilethe fluid motion is computed using the MPM. The contact forces between solid elementsand rigid walls are calculated using the DEM. The interaction between solidelements and fluid particles are calculated via an interfacial scheme within the MPMframework. With a focus on the boundary condition effect, the proposed procedure isillustrated by representative examples, which demonstrates its potential for a certaintype of engineering problems.